Peran ESG dalam Mendukung Green Economy Indonesia dalam Perspektif Perbankan Syariah - Maulana, Mohamad Riski; Pratiwi, Rizka Sobriyani; Aizza, Dianatul; Sulasih, Sulasih (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to examine the role of implementing Environmental, Social, and Governance (ESG) principles in supporting the transition toward a green economy in Indonesia from the perspective of Islamic banking. The research employs a qualitative approach using a library research method, reviewing academic literature published between 2020 and 2025. Data were analyzed through thematic content analysis to identify the alignment between ESG dimensions and maqashid shariah, as well as the challenges and opportunities of ESG implementation within Islamic banking institutions. The findings reveal that ESG application in Islamic banking remains partial, with greater emphasis on the environmental dimension through instruments such as green sukuk and green financing. The social and governance aspects have not yet been fully integrated into sustainability strategies. Nevertheless, integrating ESG with maqashid shariah strengthens the role of Islamic banks as agents of change in sustainable development. The study highlights the importance of establishing specific regulations, transparent reporting systems, and sharia-compliant green financial innovations to enhance the contribution of Islamic banking to Indonesia’s green economy.